Crystals, defects and microstructures : - Phillips, Robert Brooks (Cambridge University Press, 2001)
A central tenet of materials analysis is the structure-property paradigm, which proposes a direct connection between the geometric structures within a material and its properties. The increasing power of high-speed computation has had a major impact on theoretical materials science and has permitted the systematic examination of this connection between structure and properties. In this textbook.